An endocytosis defect as a possible cause of proteinuria in polycystic kidney disease - Obermüller, Nicholas; Kränzlin, Bettina; Blum, Werner F.; Gretz, Norbert; Witzgall, Ralph (American journal of physiology. Renal physiology, 2001)
Because proteinuria has been demonstrated in patients with autosomal-dominant polycystic kidney disease (ADPKD), we have investigated whether proteinuria also occurs in the (cy/+) rat, a widely used model for ADPKD. Increased urinary excretion of proteins, in particular of albumin, can be found in 16-wk-old (cy/+) rats, with a gel electrophoresis pattern compatible with a tubular origin of proteinuria. Using FITC-labeled dextran as an in vivo tracer for renal tubular endosomal function, we could show that portions of cyst-lining epithelia from proximal tubules have lost the ability to endocytose, which is necessary for the reabsorption of low-molecular-weight proteins. By immunohistochemistry, the expression of other proteins implicated in endocytosis, such as the chloride channel ClC-5 and the albumin receptor megalin, correlated well with the presence and absence of FITC-dextran in cysts. As an example of growth factor systems possibly being affected by this endocytosis defect, we could detect increased urinary levels of insulin-like growth factor-I protein in (cy/+) animals. These data indicate that proteinuria and albuminuria in the aforementioned rat model for ADPKD are due to a loss of the endocytic machinery in epithelia of proximal tubular cysts. This may also affect the concentration of different growth factors and hormones in cyst fluids and thus modulate cyst development.
Gesehen am 28.06.2022